HLA genotyping in Japanese patients with multiple myeloma receiving bortezomib: An exploratory biomarker study of JCOG1105 (JCOG1105A1). Issue 12 (26th October 2021) - Ri, Masaki; Iida, Shinsuke; Maruyama, Dai; Sakabe, Aya; Kamei, Ryo; Nakashima, Takuto; Tohkin, Masahiro; Osaga, Satoshi; Tobinai, Kensei; Fukuhara, Noriko; Miyazaki, Kana; Tsukamoto, Norifumi; et al.
Abstract: Bortezomib (Btz) shows robust efficacy in patients with multiple myeloma (MM); however, some patients experience suboptimal responses and show specific toxicities. Therefore, we attempted to identify specific HLA alleles associated with Btz‐related toxicities and response to treatment. Eighty‐two transplant‐ineligible patients with newly diagnosed MM enrolled in a phase II study (JCOG1105) comparing two less intensive melphalan, prednisolone, plus Btz (MPB) regimens were subjected to HLA typing. The frequency of each allele was compared between the groups, categorized based on toxicity grades and responses to MPB therapy. Among 82 patients, the numbers of patients with severe peripheral neuropathy (PN; grade 2 or higher), skin disorders (SD; grade 2 or higher), and pneumonitis were 16 (19.5%), 15 (18.3%), and 6 (7.3%), respectively. Complete response was achieved in 10 (12.2%) patients. Although no significant HLA allele was identified by multiple comparisons, several candidates were identified. HLA‐B*40:06 was more prevalent in patients with severe PN than in those with less severe PN (odds ratio [OR] = 6.76). HLA‐B*40:06 and HLA‐DRB1*12:01 were more prevalent in patients with SD than in those with less severe SD (OR = 7.47 and OR = 5.55, respectively). HLA‐DRB1*08:02 clustered in the group of patients with pneumonitis (OR = 11.34). Complete response was achieved in patients carrying HLA‐DQB1*03:02, HLA‐DQB1*05:01, and HLA‐DRB1*01:01 class II alleles. HLA genotyping could help predict Btz‐induced toxicity and treatment efficacy in patients with MM, although this needs further validation. Abstract : Four factors, HLA‐B4006, female (sex), Arm A (treatment course), and bone pain, were chosen as explanatory variables using the stepwise method. The carriers of HLA‐B4006 showed the highest odds ratio for the risk of bortezomib‐induced peripheral neuropathy.